A near miss case of placenta percreta in a patient with post myomectomy scar - Singh, Vinita; Sahu, Rajshree; Das, Esha; C., Pavan B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The term placenta accreta or placenta accrete syndrome is used to describe a spectrum of an abnormal placental implantation and firm adherence which are classified according to the depth of invasion into the uterus. A 28-year-old elderly primigravida presented AIIMS OPD to for the 1st time at 13+2 weeks of gestation with brownish discharge per vaginum. Ultrasonography done showed 12 weeks single intrauterine pregnancy with subchorionic haemorrhage of 3.7×2.52 cm with placenta being fundoanterior. She underwent myomectomy 2 years back and during her antenatal care in 3rd trimester growth scan at 30+2 weeks of gestation placenta was fundoanterior with loss of retroplacental hypoechoic in the upper margin of placenta at the myomectomy scar site with small extra uterine collection seen measuring 7.6×2.3 cm and hence possibility of placenta accreta was suggestive by the above findings confirmed by MRI. Emergency cesarean section done at 36+6 weeks of gestation for leaking per vaginum. Manual removal of placenta was tried but it failed and soon atonic PPH developed. Seeing no response with uterotonics internal iliac artery ligation was also attempted but failed. Immediate decision for hysterectomy was taken as a life-saving method. On adhesiolysis in the fundal region placental tissue perforating uterine serosa was visible on the surface of uterus, hence diagnosis of placenta percreta was confirmed which was further confirmed on histopathological report. Currently hysterectomy or local resection is preferred over conservative management with methotrexate.